PENGINTEGRASIAN PROGRAM PENDIDIKAN KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS DI SEKOLAH DASAR - Arrasyidi, Laila Amalia; Ujang Jamaludin; Istinganatul Ngulwiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Religious character is a very important character to have, considering the many cases that reflect society's current moral crisis. This religious character is very necessary to face current developments and moral degradation. This research aims to describe the background to the integration of religious education programs, planning and implementation of religious learning and the output of religious learning in the form of religious character. The results of this research show that there are several factors that influence integration, namely the importance of religious education, the lack of PAI lesson hours, the Cilegon Mayor's Perwal and the existence of a Full Day School policy. Furthermore, from religious learning planning, teachers have prepared good plans starting from formulating learning objectives, mapping learning materials, determining learning methods and media as well as learning evaluation. And have carried out learning well according to plan. Apart from that, it is also supported by religious habituation activities to shape students' religious character. so that the indicators of religious character Thinking, acting and behaving in accordance with religious teachings, Carrying out God's commands, Tolerance towards followers of other religions and living in harmony with followers of other religions can be seen in students